EFFECTIVENESS OF RUQYAH SYAR’IYYAH ON PHYSICAL DISEASE TREATMENT IN RIAU PROVINCE - Adynata Adynata; Idris Idris (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Ruqyah Syar’iyyah is one of Sunnah Prophet Muhammad in treating diseases and disorders syaithan, that is by reciting Al-Qur’an verses and praying. Most Muslims understand that ruqyah Syar’iyyah is only effectively treat non-medical disease or illness caused by psychiatric disorders and jin, whereas medical illness to be treated by medical means, Though al-Qur’an Surat al-Isra’ verses 82 mentions that al-Qur’an is as a bidder (a cure) and a mercy for believers without distinction of medications for non-medical or medical illness. Based on the research of writer in 2015, there are two methods ruqyah Syar’iyyah in Riau Province, which is manual method and practical Qur’anic Healing method. In fact, there are many chronic medical illnesses cannot be treated by doctors, but these diseases can be treated and cured by ruqyah without being accompanied by medication. Thus, ruqyah Syar’iyyah is not only effectively treat mental illness, but also effectively treat medical ailments